Effects of Cellulase and Lactiplantibacillus plantarum on the Fermentation Parameters, Nutrients, and Bacterial Community in Cassia alata Silage - Xian, Zhenyu; Wu, Jiaqi; Deng, Ming; Wang, Meng; Tian, Hanchen; Liu, Dewu; Li, Yaokun; Liu, Guangbin; Sun, Baoli; Guo, Yongqing (Frontiers in Microbiology, 2022)
Silage Cassia alata (CA) can alleviate feed shortage in some areas to a certain extent and reduce feed costs. The present research evaluated the effect of cellulase (CE) and Lactiplantibacillus plantarum (LP) on the fermentation parameters, nutrients, and bacterial community of CA silage. Chopped CA was ensiled with three different treatments, namely, no inoculant (CK), CE, and LP, and the indexes were determined on the 2nd, 6th, 14th, and 30th days of silage fermentation. The fermentation parameters indicate that the pH value of three groups decreased and then increased with the ensilage process, and the lowest value was observed at 14 days. The CK and LP groups attained the highest value at 30 days, while the CE group attained the highest value at 2 days. Additionally, the pH value and NH3-N content were significantly lower (P < 0.05) in the CE and LP groups than the CK group. In terms of nutrients, crude protein (CP) contents significantly increased (P < 0.05) in the CE and LP groups on the 30th day. The neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents of CE group were significantly and negatively associated with fermentation time, and the water-soluble carbohydrate (WSC) contents of three groups were significantly lower during ensiling. In comparison with the CK group, the NDF and ADF contents were significantly reduced (P < 0.05), and the WSC content increased (P < 0.05) in the CE group on day 30. Sequencing analysis of bacterial communities showed that Lactobacillus became the most dominant genus in the ensilage process. Moreover, both CE and LP groups increased the abundance of Lactobacillus and decreased that of Klebsiella, Weissella, and Acetobacter compared with the CK group, in which LP had a better effect. CE and LP could further improve the silage quality of CA, and LP had a greater effect in reconstructing the bacterial community in the silage environment.